2013
DOI: 10.5626/jcse.2013.7.2.122
|View full text |Cite
|
Sign up to set email alerts
|

The MPI CyberMotion Simulator: A Novel Research Platform to Investigate Human Control Behavior

Abstract: The MPI CyberMotion Simulator provides a unique motion platform, as it features an anthropomorphic robot with a large workspace, combined with an actuated cabin and a linear track for lateral movement. This paper introduces the simulator as a tool for studying human perception, and compares its characteristics to conventional Stewart platforms. Furthermore, an experimental evaluation is presented in which multimodal human control behavior is studied by identifying the visual and vestibular responses of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In both experiments, we used the Max Planck CyberMotion Simulator [20] to present participants with a large number (600-648) of unisensory visual-only and inertial-only, and multisensory visual-inertial motion stimuli, with headings ranging the full circle, and discrepancies up to ±90° (in the multisensory conditions). For each experimental trial, participants indicated the heading of self-motion using a pointer device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both experiments, we used the Max Planck CyberMotion Simulator [20] to present participants with a large number (600-648) of unisensory visual-only and inertial-only, and multisensory visual-inertial motion stimuli, with headings ranging the full circle, and discrepancies up to ±90° (in the multisensory conditions). For each experimental trial, participants indicated the heading of self-motion using a pointer device.…”
Section: Resultsmentioning
confidence: 99%
“…The stimuli were presented using the Max Planck Institute CyberMotion Simulator facility [20]. Visual stimuli showed movements through a three dimensional environment with a ground plane and limited-lifetime particles, presented stereoscopically using a dual projection system in conjunction with stereo glasses (Infitec ® GmbH, Ulm, Germany, model INFITEC ® Premium Glasses).…”
Section: Methodsmentioning
confidence: 99%
“…We now develop an SSID algorithm to estimate G ff and G fb . For each k ∈ N, define σ k ≜ e ȷθ k , and define (10) where…”
Section: Subsystem Identification Algorithmmentioning
confidence: 99%
“…SSID also has application to modeling human behavior. For example, there is interest in modeling human-inthe-loop behavior for applications such as aircraft [7][8][9][10] and automobiles [11][12][13]. In addition, SSID methods can be used to model human behavior in motor control experiments, which study human learning [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…-Robot arm system by Kuka with realization at the Max Planck Institute in Tuebingen (Nieuwenhuizen and B€ ulthoff 2013). Here the motion system is based on a production robot, which is available in large quantities and thus at relatively low cost.…”
Section: Concepts For Dynamic Driving Simulatorsmentioning
confidence: 99%